Interactions between antifungals and everolimus against Cryptococcus neoformans - Liang, Pin; Song, Jiquan; Liu, Qin (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract: Cryptococcus is the causal agent of cryptococcosis, a disease with high mortality mainly related to HIV immunosuppression and usually manifests with pneumonia and/or meningoencephalitis. There are very few therapeutic options; thus, innovative approaches are required. Herein, We examined the interaction of everolimus (EVL) with amphotericin B (AmB) and azoles [fluconazole (FLU), posaconazole (POS), voriconazole (VOR), itraconazole (ITR)] against Cryptococcus. Eighteen Cryptococcus neoforman clinical isolates were analyzed. Following the guidelines of the Clinical and Laboratory Standards Institute (CLSI) M27-A4, we conducted a broth microdilution experiment to determine the minimum inhibitory concentrations (MICs) of azoles, EVL, and AmB for assessing antifungal susceptibility. A fractional inhibitory concentration index (FICI) of less than and equal to 0.5 indicated synergy, with a range of 0.5 to 4.0 indicated indifference and a value more than 4.0 indicated antagonism. These experiments revealed that EVL had antifungal activity against C. neoforman. Moreover, EVL, POS, AmB, FLU, ITR, and VOR exhibited MIC values ranging from 0.5-2 μg/mL, 0.03125-2 μg/mL, 0.25-4 μg/mL, 0.5-32μg/mL, 0.0625-4μg/mL and 0.03125-2μg/mL, respectively. The combination of EVL with AmB and azoles (POS, FLU, ITR, and VOR) exhibited synergistic antifungal effects against 16 (88.9%), 9 (50%), 11 (61.1%), 10 (55.6%) or 6 (33.3%) of analyzed Cryptococcus strains. In the presence of EVL, the MIC values of AmB and azoles were significantly lowered. No antagonism was observed. Subsequently, in vivo analyses conducted using the G. mellonella model further confirmed that combination EVL+ POS, EVL+ FLU, and EVL+ITR treatment were associated with significantly improved larval survival following Cryptococcus spp. infection. Theses findings provide the first published evidence suggesting that a combination of EVL and AmB or azoles exhibit a synergistic effect and may be an effective antifungal disease treatment strategy for infections caused by Cryptococcus spp..